Psychological and Social Factors and Their Impact on Divorced and Married Women: A Case Study from Punjab Pakistan. Issue 5 (4th July 2022) - Zafeer, Hafiz Muhammad Ihsan; Maqbool, Samra; Yanping, Li
ABSTRACT: In Pakistani culture, family and husband are considered the strongest shelter of women. Divorce or Talaq is considered taboo; despite that, the divorce rate has risen in Pakistan for the last few years. The aim of the study was to determine the psychological and social factors and measure their impact on divorced and married women. The participants have taken from Punjab, Pakistan, and the sample consisted of 427 women. The quantitative survey method was used. The Exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA) were constituted to determine the factors and then analyzed to measure their impact through further statistical methods. The findings concluded that psychological (depression, anxiety, stress) and social (family pressure, in-laws interference, financial issues) factors significantly negatively impact on divorced and married women.